GAMBARAN PENGETAHUAN DAN SKRINING DISFAGIA OLEH PERAWAT TERHADAP PENERAPAN DOKUMENTASI PADA PASIEN DISFAGIA PASCA STROKE - Syahrun Syahrun; Alfrina Hany, Masruroh Rahayu (CV. ADIBA AISHA AMIRA, 2023)
Nurses' empowerment in screening effectively reduces pneumonia rates, improves hydration and nutrition so as to prevent further complications. Disphagia often has not been documented by nurses, due to the focus on self-care and prevention of complications. This research is a correlational description with a cross-sectional approach. The nurses working in the Stroke Unit Room and ICU consisted of 10 men and 36 women aged the majority of 25 – 31 years with a majority tenure of 18 years. A total of 30 medical records were observed, 19 cases of SNH + comorbid patients and 8 of them were dysphagia. There was a close relationship between knowledge and screening (p value 0.004) and no significant relationship between dysphagia knowledge and screening and documentation (p value 0.217). In Indonesian Nursing, thefocus is on aspiration risk, not dysphagia. Because of the lack of identification and means of being an obstacle in further management, thenurse has never received formal education. Butknowledge can be provided in self-paced, online classes. The use and adjustment of flowsheets in documentation helps in improving the workflow of completion of stroke management nursing documentation, but it takes skills and knowledge through an ethical approach to highlight the importance of communication and documentation with a patient-centered approach. The good level ofknowledge nurses about dysphagia dysphagia screening is not necessarily related to the nurse's ability to document the presence of dysphagia